Automatisk Formavsyning Volvo Powertrain Gjuteriet i Skövde: En förstudie - Bäck, Kristian; Hagman, Anton (My University, 2020)
In the foundry at Volvo Powertrain in Skövde the quality inspection of sand moulds used for casting iron is currently done manually by an operator. This is a monotonous work with some safety risks due to the age of the production line. Volvo is planning on constructing a new foundry where the safety risks of manual quality inspection is unacceptable. To solve this issue Volvo is planning to move the operator away from the inspection station to inspect the moulds from a remote location using visual aid. Volvo however is also looking into the possibility of fully automating the quality inspection. This thesis is a pre-study concerning the possibility of automating the quality inspection of sand moulds. To explore the different possibilities, suppliers of 3D-scanning and vision systems were contacted using a “Request for information”. To evaluate different solutions a requirements specification was developed. The suppliers were evaluated by using an elimination matrix and Pughs matrix with the requirements specification as the foundation for the evaluation process. After the evaluation process a test was conducted with the supplier of the solution deemed most fitting. From this test the conclusion could be drawn that it is possible to move the operator away for remote quality inspection. The test also showed that it would be possible to automate the quality inspection using AI based vision systems.